PELAKSANAAN STRATEGI PEMBELAJARAN DALAM PENDIDIKAN ISLAM - Nurrita, Teni (Asosiasi Dosen PTKIS Indonesia, 2022)
Learning strategy is a plan to achieve learning objectives by using all learning resources, media, methods in an effort to teach students. Islamic education is an activity carried out to develop all human potential by instilling the values of Islamic teachings in its adherents so that they become a person of faith, physically strong, mentally and spiritually healthy and intelligent, with noble character so that it will manifest into deeds, good for the community. needs of self and others. Learning strategies can be done by studying concepts first to find conclusions by starting with abstract things and then slowly moving towards concrete things. Learning strategies can be carried out in a group of social communities through an extension process where someone explains a material by going directly into the community to achieve learning objectives carried out by the teacher together with students to achieve the desired results by the teacher by using learning resource media so that they can determine strategy to be used. Islamic education learning strategies that are relevant and effective in teaching Islamic teachings are expository strategies, inquiry strategies and social inquiry strategies. The learning strategy that is made must contain goodness in the field of Islamic education and as a means to get closer to Allah SWT and be able to solve various existing educational problems so that Islamic education is increasingly advanced and developed.